Ground-based detection of circumnuclear Keplerian disks of ionized gas in early-type disk galaxies - Funes, J; Bertola, F; Cappellari, M; Corsini, E; Pizzella, A; Beltran, J (1999)
We demonstrate the possibility of detecting mass concentrations (down to the level of 5 x 10(7) M.) in the center of galaxies with ground-based optical telescopes properly equipped, using Keplerian gaseous disks as probes. We predict that the high spatial resolution of HST equipped with STIS will allow to detect central mass concentrations down to the level of 5 x 10(6) M.. As a consequence, the detection of low mass concentrations in the range 10(6) - 10(7) M. will constitute a very appropriate use of HST.